How we become ill: Investigating emergent properties of biological systems could help to better understand the pathology of diseases. (27th February 2017) - Finzer, Patrick
Abstract : Biological systems from single cells to whole organisms show emergent properties that are characteristic of complex systems. Understanding the emergence of new properties and the principles that govern it can help us to understand complex diseases and improve early diagnostic.